Clone, identification and functional character of two toll-like receptor 5 molecules in Schizothorax prenanti. Issue 95 (December 2019) - Du, Xiaogang; Li, Dong; Li, Yunkun; Wu, Jiayu; Huang, Anqi; Bu, Guixian; Meng, Fengyan; Kong, Fanli; Cao, Xiaohan; Han, Xingfa; Pan, Xiaofu; Yu, Guozhi; et al.
Abstract: Mammal Toll-like receptor 5 (TLR5) can directly recognize bacterial flagellin, initiate the inflammatory signaling cascades and trigger body immune system to clear the "non-self" substances. In teleosts, TLR5 has presented more complexes not only in increasing the molecular types, but also in elevating the functional diversity. In this study, we identified two TLR5 family members in Schizothorax prenanti, named as spTLR5-1 and spTLR5-2. The complete coding sequence (CDS) of spTLR5-1 is 2622 bp, encoding 873 amino acids, while the complete CDS of spTLR5-2 is 2640 bp, encoding 879 amino acids. Phylogenetic analysis showed that spTLR5-1 and spTLR5-2 were clustered to the TLR5 of schizothorax richardsonii and Cyprinus carpio respectively. The 3D structure analysis exhibited that the α-helix, β-sheet, and the ligand binding site of spTLR5-1, spTLR5-2 and human TLR5 have large differences. The spTLR5-1 and spTLR5-2 had extensively expressed in various tissues, including the higher expression in liver, spleen and head kidney. Both the expression levels of spTLR5-1 and spTLR5-2 were significantly up-regulated after Aeromonas hydrophila ( A. hydrophila ) challenge. And, the downstream genes, such as AP-1, IKK-α, NF-kB, IL-1β, IL-8 and TNF-α, were also significantly up-regulated after A. hydrophila challenge. Apart from that, the luciferase reporter assay demonstrated that the co-transfection of spTLR5-1 or spTLR5-2 into HEK293T cells showed the significantly increased NF-kB luciferase activity after flagellin stimulation. In conclusion, our results reveal that both two molecular types of fish TLR5 may commonly mediate the recognition of flagellin and the activation of the downstream inflammatory signaling molecules. Highlights: spTLR5-1 and spTLR5-2 have similar structures and localize on the cell membrane. Both spTLR5-1 and spTLR5-2 could respond to Aeromonas hydrophila challenge. Both spTLR5-1 and spTLR5-2 could significantly activated NF-κB signaling pathway upon flagellin stimulation.